2016
DOI: 10.1016/j.ijrobp.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Edema and Seed Displacements Affect Intraoperative Permanent Prostate Brachytherapy Dosimetry

Abstract: Intraoperative CBCT D90 showed a greater correlation with the day 30 dosimetry than intraoperative TRUS. Edema seemed to cause most of the systematic difference between the intraoperative and day 30 dosimetry. Seeds near the rectal wall showed the most displacement, comparing TRUS and CBCT, probably because of TRUS probe-induced prostate deformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Recently, Taussky et al reported that intraoperative USD was predictive of Day 30 dosimetry but with low predictive power due to intraprostatic seed migration and other intraoperative factors that are unpredictable in USD, and biochemical recurrence-free rate was not dependent on any intraoperative USD dosimetry parameters (22). A few groups combined intraoperative CT with TRUS and performed intraoperative adaptive plan modification similarly as our approach, demonstrating improved prostate dose coverage and correlation with Day 30 (15, 23, 24) and Day 0 (15) dosimetry. However, these approaches require a specific CT system, for example, O-arm or C-arm cone-beam CT that is not commonly available in many hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Taussky et al reported that intraoperative USD was predictive of Day 30 dosimetry but with low predictive power due to intraprostatic seed migration and other intraoperative factors that are unpredictable in USD, and biochemical recurrence-free rate was not dependent on any intraoperative USD dosimetry parameters (22). A few groups combined intraoperative CT with TRUS and performed intraoperative adaptive plan modification similarly as our approach, demonstrating improved prostate dose coverage and correlation with Day 30 (15, 23, 24) and Day 0 (15) dosimetry. However, these approaches require a specific CT system, for example, O-arm or C-arm cone-beam CT that is not commonly available in many hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Ishiyama et al (24) and Westendorp et al (23) where intraoperative CT dosimetry was compared to 1-month postoperative CT, USD and iRUF dosimetry were compared to Day 1 CT/MRI dosimetry in this study, as Day 1 CT/MRI provided dosimetry that was measured at the closest feasible time point to the treatment and therefore likely to be most similar to intraoperative readings. In this comparison, iRUF showed lower mean absolute differences and higher correlations to CT/MRI than USD for all three dosimetric parameters examined.…”
Section: Discussionmentioning
confidence: 99%
“…Seed deviation and resulting dosimetry change caused by edema between USD/iRUF and Day 1 CT/MRI was spatially-varying rather than systematic depending on the order of implantation. Unlike Ishiyama et al [7] and Westendorp et al [8] who compared intraoperative CT dosimetry to 1-month CT where differences of edema effect would be greater, we compared to Day 1 CT/MRI in which anatomy change by edema is less significant. Therefore, we believe using ICC to measure correlation is reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has demonstrated that improved dosimetric results can be achieved by combining another imaging modality, most commonly x-ray imaging with TRUS for intraoperative source localization. Recently, Ishiyama et al [7] and Westendorp et al [8] reported that intraoperative dosimetry based on O-arm CT or C-arm cone-beam CT showed higher predictive power for 1-month CT-based post-implant dosimetry than USD, demonstrating the utility of intraoperative CT imaging in combination of TRUS for improving dosimetry prediction. Unfortunately, these approaches require equipment that is not commonly available or significantly alter the current brachytherapy workflow, e.g., requiring a surgical suite with an isocentric fluoroscopic simulator, CT scanner or CT-capable C-arm, or transporting the patient to a separate room for CT scanning prior to completion of brachytherapy [7]–[12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the known limitations of PAI assessment by axial imaging (MRI or CT) and the differences in image acquisition between these modalities, the results from this paper suggest that MRI can be substituted for CT given the strong correlation (R=0.783, similar AUC's), and provide a quick easy test of PAI without the additional cost and low dose radiation exposure associated with a dedicated CT assessing for PAI. Furthermore, studies of prostate brachytherapy seed displacement caused by the presence of a transrectal device have demonstrated that the primary source of deformation from this device occurs in the posterior aspect of the prostate, which would not be expected to cause significant changes in pubic arch assessment (18, 19). Second, the use of TRUS based simulation in-lieu of attempted needle passage in an operating room to define PAI presents some potential concerns.…”
Section: Discussionmentioning
confidence: 99%